2014
DOI: 10.15567/mljekarstvo.2014.0406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bee pollen supplement on antimicrobial, chemical, rheological, sensorial properties and probiotic viability of fermented milk beverages

Abstract: In this research, effect of bee pollen supplement on antimicrobial, chemical, rheological, sensorial properties and probiotic viability of fermented milk beverages was studied. Bee pollens were added in the rate of 2.5 mg•mL-1 (B), 5 mg•mL-1 (C), 7.5 mg•mL-1 (D), 10 mg•mL-1 (E), and 20 mg•mL-1 (F). Control sample (A) was not supplemented with bee pollen. Control and supplemented milk samples were fermented by a commercial ABT1 starter culture (Chr. Hansen, Hørsholm, Denmark) containing Lactobacillus acidophilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
10
26
0
2
Order By: Relevance
“…alternatively, in the coded units: The number of variants of experiments, required to determine an impact of the set of factors Х 1 , Х 2 , Х 3 on the process of shredding, will be calculated by raising the power 2 3 :…”
Section: Results Of Research Into Quality Of the Shredded Bee Pollen mentioning
confidence: 99%
See 2 more Smart Citations
“…alternatively, in the coded units: The number of variants of experiments, required to determine an impact of the set of factors Х 1 , Х 2 , Х 3 on the process of shredding, will be calculated by raising the power 2 3 :…”
Section: Results Of Research Into Quality Of the Shredded Bee Pollen mentioning
confidence: 99%
“…By using the mean actual values, we shall calculate regression coefficients from formulae (2), (3). The regression equation (1), in this case, takes the following form:…”
Section: Results Of Research Into Quality Of the Shredded Bee Pollen mentioning
confidence: 99%
See 1 more Smart Citation
“…BG 111284, Pat. UA 37155 U), [1][2][3]. Bee pollen [4][5][6], that exceeds all widely known preparations [7] by the composition and so by possibilities of the influence on the human organism is especially valuable among them.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been found that the effects of honey on the probiotic bacteria (Ustunol & Gandhi, 2001;Shin & Ustunol, 2005) and yoghurt bacteria (Varga, 2006) were sufficiently investigated. But, the effects of pollen and royal jelly on the growth of probiotic bacteria have not been studied in detail (Nabas et al, 2014;Yerlikaya, 2014). Different results have been found due to the materials and methods used, and the growth environment tested.…”
Section: Introductionmentioning
confidence: 99%